100 Things to Know About Food - Sam Baer (Bharat Harper Collins, 2020)
This informative book is filled with 100 fascinating facts about food, from how to grow a burger in a laboratory to how many bees it takes to fill an orchard with apples. With bright, infographic-style illustrations, detailed facts on every page, a glossary and index, plus internet links to specially selected websites for more information.
Keywords: Innovations And Inventions -- Innovations And Inventions; Food And Farming -- Food And Farming